INOVASI PEMBUATAN ALAT PENGASAPAN IKAN TIPE DRUM SEBAGAI INSTRUMEN PENGOLAHAN HASIL WADUK DESA UTEUN DAMA, PEUREULAK - Mulia Safrida Sari; Ahmad Ihsan; Ida Ratna Nila; Rachmad Almi Putra; Fitriani; Suri Purnama Febri; Andri Yusman Persada; Beni Al Fajar (Fakultas Teknik, Universitas Samudra, 2023)
Uteun Dama Village is a village in Peureulak Sub-district that has the potential for reservoir products such as tilapia. The manufacture of fish smoking equipment using used drums aims to maintain the quality and nutritional value, provide a distinctive aroma, and extend the shelf life of tilapia to be longer. The making of this fish smoking equipment can be made through designing a fish smoking equipment design using the Auto Cad application and then printed to facilitate the making of a tool frame equipped with a closing door, chimney, smoking rack and furnace. The fish smoking equipment that has been made can be an alternative instrument in fish preservation with several characteristics including a larger fish smoking volume capacity, has better temperature control, can maintain sterile conditions and avoid contamination during fish storage, high fuel use efficiency and can save operational costs in the long term.